Influência da intensidade de radiação solar sobre o crescimento e a fixação simbiótica de nitrogênio pela soja (Glycine max) - Rocha, H.M.; Alvim, P. de T; DOBEREINER, J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The authors studied the effect of solar radiation intensity on growth (Dry weight, Relative growth rate, and Net assimilation rate) and on nitrogen fixation by soybean (Glycine max) inoculated with Rhizobium and grown in sand culture. The plants were grown under four conditions of solar radiation intensity, controlled by shading with "Saran" plastic screenings 27, 45, 70 and 100 per cent (no shade). The results showed that N fixation increased in proportion to solar radiation intensity. The increase was due to better growth of individual nodules and was not related to the number of nodules produced per plant. It was found also that the symbiotic fixation of N has practically no effect on growth during the first month after planting.